Unveiling the Emergent Traits of Chiral Spin Textures in Magnetic Multilayers. Issue 6 (2nd January 2022) - Chen, Xiaoye; Lin, Ming; Kong, Jian Feng; Tan, Hui Ru; Tan, Anthony K.C.; Je, Soong‐Geun; Tan, Hang Khume; Khoo, Khoong Hong; Im, Mi‐Young; Soumyanarayanan, Anjan
Abstract: Magnetic skyrmions are topologically wound nanoscale textures of spins whose ambient stability and electrical manipulation in multilayer films have led to an explosion of research activities. While past efforts focused predominantly on isolated skyrmions, recently ensembles of chiral spin textures, consisting of skyrmions and magnetic stripes, are shown to possess rich interactions with potential for device applications. However, several fundamental aspects of chiral spin texture phenomenology remain to be elucidated, including their domain wall (DW) structure, thermodynamic stability, and morphological transitions. Here the evolution of these textural characteristics are unveiled on a tunable multilayer platform—wherein chiral interactions governing spin texture energetics can be widely varied—using a combination of full‐field electron and soft X‐ray microscopies with numerical simulations. With increasing chiral interactions, the emergence of Néel helicity, followed by a marked reduction in domain compressibility, and finally a transformation in the skyrmion formation mechanism are demonstrated. Together with an analytical model, these experiments establish a comprehensive microscopic framework for investigating and tailoring chiral spin texture character in multilayer films. Abstract : Magnetic skyrmions are chiral spin textures with nanoscale size and ambient stability—promising for unconventional computing applications. Here, with increasing interfacial chiral interactions, sequential transitions in the chiral microstructure, thermodynamic stability, field evolution, and formation mechanism of skyrmions are unveiled. Using complementary microscopy techniques and an analytical model, a framework for tailoring spin texture character is established in multilayer films.